Biological relevance of citrullinations: diagnostic, prognostic and therapeutic options. (March 2015) - Gudmann, Natasja S.; Hansen, Niels U. B.; Jensen, Anne C. B.; Karsdal, Morten A.; Siebuhr, Anne S.
Abstract Objective: Citrullination has become a hot topic within recent years due to its involvement in diseases such as rheumatoid arthritis (RA), multiple sclerosis and fibrosis. Citrullinations are the conversion of arginine to citrulline by peptidylarginine deiminase (PAD) enzymes, which affect protein properties. The aim of this review is to summarize the advances in citrullination research and further explore the potential of citrullination as a diagnostic tool as well as inhibition of PAD enzymes as a target for treatment. Method: We reviewed current literature with emphasis on the role of citrullination in health and disease, the nature of enzymes responsible for citrullination, and the potential of applying citrullinations in diagnostics and pharmaceuticals. Conclusion: Current literature suggests that increased levels of citrullinated proteins are found in several if not all inflammatory diseases. In RA measurement of anti-citrullinated protein antibodies (ACPA) against citrullinated protein fragments are widely used as a prognostic biomarker. More recently, it has been indicated that levels of selected citrullinated proteins carries additional potential as biomarkers. This includes citrullinated vimentin which provide prognostic information in diseases as fibrosis and ankylosing spondylitis. In addition, recent studies suggest that inhibition of PAD is a target for treatment of diseases such as RA and cancer where proteins that are citrullinated are believed to influence the disease activity.